Transcatheter coil occlusion of patent ductus arteriosus and follow-up results - Sezen Ugan Atik; İrfan Levent Saltık (KARE Publishing, 2019)
Objective: Although many articles have been published about transcatheter coil occlusion, few studies have been conducted on the long-term outcomes of patent ductus arteriosus closure with a coil. This study is an examination of the follow-up data of patients who underwent transcatheter patent ductus arteriosus closure with a coil. Methods: Between May 1996 and May 2018, 243 patients underwent transcatheter patent ductus arteriosus closure with a coil. The patients were divided into 2 groups based on the timing of the use of ductal occluders at the facility. Until the end of 2005, every ductus was closed with a coil. Since initiating the use of ductal occluders in 2006, coils are mostly used to close small, elongated ducts, and occasionally, some complex ducts. Results: The median age of the patient was 4.33 years, the median weight was 15 kg, and the median duct diameter was 2 mm. In this study group, 98 (40%) patients were male and 145 were female (60%). The angiographic features of the ductus were classified as type A in 126 patients, type B in 15, type C in 6, type D in 9, type E in 74, and 13 were recorded as other types. In 238 of the patients, the patent ductus arteriosus was successfully closed with a coil. In 5 (2.2%) cases, the procedure was unsuccessful. Echocardiography follow-up continued for an average of 4.1+-4.1 years (1 day-19 years). A residual shunt was observed in 42 patients, and spontaneous occlusion was seen in 29 of the 42 patients. Conclusion: The results of this study indicated that closure of the patent ductus arteriosus with a coil was a safe and effective method.